Secondary battery and electronic device
By using a specific combination of the positive electrode active material layer and electrolyte in lithium-ion batteries, the problems of stability and environmental friendliness of traditional bonding materials are solved, the flexibility and high-temperature storage characteristics of the battery are improved, and the low-temperature internal resistance is reduced.
Patent Information
- Application Number
- CN202411918335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-03-21
AI Technical Summary
The polyvinylidene difluoride (PVDF) bonding material used in existing lithium-ion batteries is prone to gelation, resulting in a decrease in slurry stability and affecting battery performance. The R142B used in its preparation process is a high-risk environmental pollutant that does not meet the requirements of green and sustainable development.
By adjusting the positive electrode composition and electrolyte composition in the secondary battery, the positive electrode active material layer includes the positive electrode active material and polyamide imide, and the electrolyte includes a compound with sulfur-oxygen double bond and lithium difluorophosphate to improve the flexibility of the positive electrode, reduce low-temperature internal resistance and improve high-temperature storage characteristics.
This design not only improves the flexibility of the positive electrode, reduces the low-temperature internal resistance of the secondary battery, but also improves the storage characteristics at high temperatures, solving the problems of stability and environmental friendliness of traditional bonding materials.
Smart Images

Figure BDA0005207605390000101 
Figure BDA0005207605390000111 
Figure BDA0005207605390000121
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of August 14, 2024, an application number of 202411113343.9, and an invention name of “Secondary Battery and Electronic Device”. Technical Field
[0002] The present application relates to the field of energy storage, and in particular to a secondary battery and an electronic device. Background Art
[0003] Lithium-ion batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used for a wide range of purposes. Lithium-ion batteries usually have battery components such as a positive electrode, a negative electrode, and a separator that separates the positive electrode from the negative electrode. An electrode (such as a positive electrode or a negative electrode) usually has a current collector and an electrode composite material layer formed on the current collector. For example, the positive electrode composite material layer is usually formed by applying a positive electrode slurry on the current collector and drying it. The positive electrode slurry is formed by containing a positive electrode active material, a conductive material for improving conductivity, and a bonding material for bonding these components in a dispersion medium. In addition, polyvinylidene fluoride (PVDF) and the like have been used as bonding materials used to form the positive electrode composite material layer. PVDF is prone to gelling, resulting in decreased slurry stability and affecting battery performance. PVDF is a fluorine-containing binder, and its polymer monomer VDF is prepared by dehydrochlorination of 1,1-difluoro-1-chloroethane (R142B). However, R142B is a highly dangerous environmental pollutant and does not meet the requirements of green and sustainable development of the new energy industry. Developed countries such as the European Union are gradually restricting its use in lithium batteries. Summary of the invention
[0004] The embodiments of the present application solve the problems existing in the prior art to some extent by adjusting the positive electrode composition and the components in the electrolyte used in the secondary battery. The inventors found that the positive electrode active material layer includes a positive electrode active material and polyamide-imide, and the electrolyte includes a compound having a sulfur-oxygen double bond and lithium difluorophosphate, which can not only improve the flexibility of the positive electrode, but also reduce the internal resistance of the secondary battery at low temperature and improve the storage characteristics at high temperature, thereby completing the present invention.
[0005] In some embodiments, the positive electrode active material layer further includes an auxiliary agent, and the auxiliary agent includes at least one of pentaerythritol tetrabenzoate, trimethyl citrate, triethyl citrate, tributyl citrate, or sodium ditridecyl sulfosuccinate.
[0006] In some embodiments, relative to 100 parts by mass of the electrolyte, the compound having a sulfur-oxygen double bond is in an amount of 0.05 parts by mass to 2.9 parts by mass, and / or the lithium difluorophosphate is in an amount of 0.02 parts by mass to 0.59 parts by mass.
[0007] In some embodiments, the compound having a sulfur-oxygen double bond includes a sulfonate and / or a sulfate.
[0008] In some embodiments, the sulfonate ester includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone or methylene disulfonate.
[0009] In some embodiments, the sulfate ester includes at least one of ethylene sulfate or propylene sulfate.
[0010] In some embodiments, the electrolyte further includes an additive C, and the additive C includes at least one of adiponitrile, hexamethyldisiloxane, 1,3-divinyltetramethyldisiloxane, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium tetrafluoro(oxalato)phosphate, or lithium difluorobis(oxalato)phosphate.
[0011] In some embodiments, the total amount of the additive C is 0.1 parts by mass to 3 parts by mass relative to 100 parts by mass of the electrolyte.
[0012] In some embodiments, relative to 100 parts by mass of the electrolyte, at least one of the following conditions is satisfied:
[0013] 1) The adiponitrile is 0.1 to 2.4 parts by mass;
[0014] 2) the hexamethyldisiloxane is 0.01 to 0.6 parts by mass;
[0015] 3) the 1,3-divinyltetramethyldisiloxane is 0.01 to 1 parts by mass;
[0016] 4) the lithium bis(oxalato)borate is 0.01 to 0.5 parts by mass;
[0017] 5) the lithium difluoro(oxalato)borate is 0.01 to 0.5 parts by mass;
[0018] 6) The lithium tetrafluoro(oxalato)phosphate is in an amount of 0.01 to 0.5 parts by mass;
[0019] 7) The lithium difluorobis(oxalato)phosphate is in an amount of 0.01 to 0.7 parts by mass.
[0020] In another aspect of the present application, the present application provides an electronic device, which includes the secondary battery described in the present application.
[0021] The present application uses a specific positive electrode structure and electrolyte combination, which can not only improve the flexibility of the positive electrode, but also reduce the internal resistance of the secondary battery at low temperatures and improve the storage characteristics at high temperatures.
[0022] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0023] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0024] Unless expressly stated otherwise, the following terms used in this application have the meanings indicated below.
[0025] The present application uses a specific positive electrode structure and electrolyte combination, which can not only improve the flexibility of the positive electrode, but also reduce the internal resistance of the secondary battery at low temperatures and improve the storage characteristics at high temperatures.
[0026] In one embodiment, the present application provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte as described below.
[0027] I. Positive electrode
[0028] The present application relates to a secondary battery and an electronic device. Specifically, the present application provides a secondary battery, which includes: a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material and polyamide-imide, and the electrolyte includes a compound having a sulfur-oxygen double bond and lithium difluorophosphate, which can not only improve the flexibility of the positive electrode, but also reduce the internal resistance of the secondary battery at low temperature and improve the storage characteristics at high temperature.
[0029] The positive electrode includes a positive electrode collector and a positive electrode active material layer disposed on a surface of the positive electrode collector.
[0030] The positive electrode active material layer contains a positive electrode active material, and the positive electrode active material layer may be one layer or multiple layers. The positive electrode active material is any material that can reversibly insert and release lithium ions.
[0031] The inventors unexpectedly discovered in the experiment that, during the mixing process of the positive electrode, the addition of a binder, polyamide-imide, improved the flexibility of the electrode, but increased the internal resistance of the electrode, especially at high temperatures, the electrode cracked and the active material layer broke brittlely and powdered. The inventors further discovered that the electrode can significantly reduce the internal resistance of the electrode in an electrolyte system containing a compound having a sulfur-oxygen double bond and lithium difluorophosphate. The reason is speculated to be that polyamide-imide is prone to swelling in a carbonate electrolyte system, resulting in an increase in internal resistance, while compounds having a sulfur-oxygen double bond and lithium difluorophosphate significantly inhibit the swelling, thereby reducing the internal resistance of the electrode. This can not only improve the flexibility of the positive electrode, but also reduce the internal resistance of the secondary battery at low temperatures and improve the storage characteristics at high temperatures.
[0032] Specifically, from the viewpoint of improving positive electrode flexibility, relative to 100 parts by mass of positive electrode materials (including positive electrode active material, conductive agent, binder, optional auxiliary agent), the mass of the polyamide-imide is 0.3 parts by mass to 3 parts by mass. The mass of polyamide-imide is preferably less than 3 parts by mass, more preferably less than 2.5 parts by mass, further preferably less than 2 parts by mass, particularly preferably less than 1.5 parts by mass, preferably more than 0.3 parts by mass, more preferably more than 0.5 parts by mass. When the mass of polyamide-imide is within the above range, it is possible to effectively improve the flexibility of the positive electrode.
[0033] Specifically, the polyamideimide may have any molecular weight, but preferably has a number average molecular weight in the range of 10,000 to 40,000 in order to further improve the solubility of the polyamideimide in the solvent. The number average molecular weight is measured by gel permeation chromatography.
[0034] Specifically, from the viewpoint of improving the flexibility of the positive electrode, the positive electrode active material layer further includes an auxiliary agent, and the auxiliary agent includes at least one of pentaerythritol tetrabenzoate, trimethyl citrate, triethyl citrate, tributyl citrate or sodium ditridecyl sulfosuccinate. The auxiliary agent can not only improve the flexibility of the positive electrode, but also inhibit the compound having a sulfur-oxygen double bond and lithium difluorophosphate from forming an excessively thick film on the surface of the positive electrode.
[0035] The positive electrode active material is any material that can reversibly embed and deintercalate lithium ions. For example, as a positive electrode active material for a secondary battery, a composite metal oxide containing one or more selected from the group consisting of cobalt, manganese, and nickel and lithium, or an olivine-type phosphate containing one or more selected from iron, cobalt, nickel, and manganese is used. These positive electrode active materials can be used alone or in combination of two or more.
[0036] As such lithium composite metal oxides, for example, LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Nix O2 (0.01 < x < 1), LiNi x Mn y Co z O2 (x + y + z = 1), a solid solution of Li2MnO3 and LiMO2 (M is a transition metal such as Co, Ni, Mn, Fe), LiNi 1 / 2 Mn 3 / 2 O4, LiFePO4, LiMnPO4, and LiMn 1-x Fe x PO4 (0.01 < x < 1) or more, more preferably 2 or more. A part of these composite metal oxides with lithium or olivine-type phosphates containing lithium can be replaced by other elements, or a part of cobalt, nickel, manganese, and iron can be replaced by one or more elements selected from Co, Mn, Ni, Mg, Al, B, Ti, V, Nb, Cu, Zn, Mo, Ca, Sr, W, and Zr, or coated with a compound containing these other elements or a carbon material.
[0037] Regarding the voltage during charging, from the perspective of increasing the voltage, the positive electrode potential is preferably 4.4 V (vs. Li / Li + ) or more, more preferably 4.5 V (vs. Li / Li + ) or more, and particularly preferably 4.6 V (vs. Li / Li + ) or more.
[0038] There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon blacks such as acetylene black; carbon materials such as amorphous carbon like needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials can be used alone or in any combination.
[0039] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it can dissolve or disperse the positive electrode active material, conductive material, and positive electrode binder. Examples of solvents used to form the positive electrode slurry may include either aqueous solvents or organic solvents. Examples of aqueous media may include, but are not limited to, water and mixed media composed of alcohol and water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0040] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0041] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0042] The positive electrode can be made by forming a positive electrode active material layer containing a positive electrode active material and a binder on the positive electrode current collector. The manufacture of the positive electrode using the positive electrode active material can be carried out by conventional methods, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.
[0043] II. Electrolyte
[0044] The electrolyte used in the secondary battery of the present application includes an electrolyte and a solvent for dissolving the electrolyte. In some embodiments, the electrolyte of the present application includes a compound having a sulfur-oxygen double bond and lithium difluorophosphate.
[0045] Since polyamide-imide is prone to swelling in carbonate electrolyte systems, the inventors have found that when the electrolyte contains a compound with a sulfur-oxygen double bond and lithium difluorophosphate, the swelling can be significantly inhibited, which not only improves the flexibility of the positive electrode, but also reduces the internal resistance of the secondary battery at low temperatures and improves the storage characteristics at high temperatures.
[0046] Specifically, from the perspective of improving the high temperature storage characteristics of the secondary battery, in some embodiments, relative to 100 parts by mass of the electrolyte, the mass of the compound having a sulfur-oxygen double bond is a part by mass, and the value range of a is 0.05 to 3. In some embodiments, the value range of a is 0.05 to 2.9. In some embodiments, the value range of a is 0.25 to 2.16. In some embodiments, the value range of a is 1.35 to 2.9. In some embodiments, a is 0.05, 0.25, 0.35, 0.52, 0.65, 0.78, 0.82, 1.35, 1.50, 1.88, 2.16, 2.45, 2.66, 2.90 or in the range consisting of any two of the above values. For example, 0.05 to 1.35, 0.25 to 1.50, 0.35 to 1.88, 0.65 to 2.16, and 0.82 to 2.66. When the content is within the above range, it contributes to further improving the storage characteristics at high temperatures.
[0047] Specifically, the compound having a sulfur-oxygen double bond includes sulfonate esters and / or sulfate esters.
[0048] The sulfonate ester includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone or methylene methanedisulfonate.
[0049] The sulfate ester includes at least one of ethylene sulfate or propylene sulfate.
[0050] The compound having a sulfur-oxygen double bond may be only one or more than one. If there are two or more lithium difluorophosphates, a is the total content. Preferably, 1,3-propane sultone and ethylene sulfate are used in combination, which can further improve the storage characteristics of the secondary battery at high temperature.
[0051] Specifically, from the perspective of improving the storage characteristics of the secondary battery at high temperature, in some embodiments, relative to 100 parts by mass of the electrolyte, the mass of lithium difluorophosphate is b parts by mass, and the value range of b is 0.02 to 0.59. In some embodiments, the value range of b is 0.05 to 0.38. In some embodiments, the value range of b is 0.12 to 0.59. In some embodiments, b is 0.02, 0.03, 0.05, 0.07, 0.12, 0.16, 0.27, 0.38, 0.45, 0.59 or in the range consisting of any two of the above values. For example, 0.02 to 0.12, 0.03 to 0.38, 0.05 to 0.59, 0.12 to 0.38, 0.27 to 0.59, when within the above range, it helps to further improve the storage characteristics at high temperature.
[0052] In addition, the electrolyte may further include an additive C, which includes at least one of adiponitrile, hexamethyldisiloxane, 1,3-divinyltetramethyldisiloxane, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium tetrafluoro(oxalato)phosphate, or lithium difluorobis(oxalato)phosphate. The additive C may be only one or more.
[0053] The inventors also unexpectedly discovered that additive C can not only inhibit the decomposition of polyamide-imide during the charge and discharge process, but also further reduce the impedance of compounds with sulfur-oxygen double bonds and lithium difluorophosphate coatings, thereby further improving the flexibility of the positive electrode, reducing the internal resistance of the secondary battery at low temperatures and improving the storage characteristics at high temperatures.
[0054] The content of the additive C is 0.1 parts by mass or more relative to 100 parts by mass of the electrolyte, preferably 0.1 parts by mass or more, preferably 0.28 parts by mass or more, more preferably 0.60 parts by mass or more. In addition, from the viewpoint of reducing the internal resistance of the secondary battery at low temperature, the content of the additive C is 3 parts by mass or less, preferably 2.82 parts by mass or less, more preferably 2.55 parts by mass or less, and further preferably 1.86 parts by mass or less.
[0055] The lithium salt used in the electrolyte of the present application includes lithium hexafluorophosphate, and the content of lithium hexafluorophosphate is 9% to 15% by mass, preferably 9% to 13% by mass, and more preferably 9% to 12% by mass, based on the total mass of the electrolyte. By setting the content range to the above, the internal resistance at low temperature and the storage characteristics at high temperature can be improved in a more balanced manner.
[0056] The electrolyte of the present application may further include any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte. For example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, and sulfur-containing organic solvents. Chain carboxylates are preferred, such as ethyl acetate, ethyl fluoroacetate, ethyl propionate, and propyl propionate.
[0057] In some embodiments, the electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. The quality of the electrolyte is not particularly limited as long as it does not impair the effects of the present application.
[0058] III. Negative electrode
[0059] The negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active material layer contains a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0060] As a current collector for holding the negative electrode active material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.
[0061] There is no particular limitation on the negative electrode active material, as long as it can reversibly absorb and release lithium ions. Examples of negative electrode active materials may include, but are not limited to, carbon materials such as natural graphite and artificial graphite; metals such as silicon (Si) and tin (Sn); or oxides of metal elements such as Si and Sn. Negative electrode active materials may be used alone or in combination.
[0062] The negative electrode active material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the negative electrode current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0063] The negative electrode can be prepared by applying a negative electrode mixture slurry containing a negative electrode active material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode active material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.
[0064] IV. Isolation membrane
[0065] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0066] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polyether sulfones, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.
[0067] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0068] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0069] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a resin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.
[0070] The thickness of the isolation film is arbitrary. In some embodiments, the thickness of the isolation film is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation film is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the isolation film is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0071] The present application further provides an electronic device, which includes the secondary battery described in the present application.
[0072] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0073] The preparation of the secondary battery is described below in conjunction with specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.
[0074] Preparation of secondary batteries
[0075] The positive electrode active material lithium cobalt oxide (97 parts by mass) and acetylene black (1.5 parts by mass) are mixed, added to a solution obtained by dissolving polyamide-imide (HR-16NN of Toyobo Co. Ltd., 1.5 parts by mass) in 1-methyl-2-pyrrolidone in advance, and mixed to prepare a positive electrode mixture paste. The positive electrode mixture paste is applied to an aluminum foil, dried, pressurized, and cut into a specified size to make a positive electrode. If an auxiliary agent is added (as shown in Table 1-1), the content of polyamide-imide is adjusted to 1.3 parts by mass and the auxiliary agent is 0.2 parts by mass.
[0076] The negative electrode active material artificial graphite and silicon carbon (mass ratio 97:3, totaling 96 parts by mass) and styrene-butadiene rubber (2 parts by mass) were mixed and added to a solution obtained by dissolving lithium carboxymethyl cellulose (2 parts by mass) in deionized water in advance and mixed to prepare a negative electrode mixture paste. The negative electrode mixture paste was applied to a copper foil, dried, pressurized, and then cut into a specified size to make a negative electrode.
[0077] A 5 μm polyethylene porous film was used as a separator.
[0078] The positive electrode and negative electrode prepared as above are each connected to a wire. The layers are stacked and wound via the above-mentioned separator. In addition, LiPF6 as a supporting electrolyte is dissolved in a solution containing ethylene carbonate, propylene carbonate, propyl propionate, a compound having a sulfur-oxygen double bond, lithium difluorophosphate, and an additive C. Based on 100 parts by mass of the total mass of the electrolyte, the mass content and components of the compound having a sulfur-oxygen double bond, lithium difluorophosphate, and additive C are shown in Tables 1-2, 2, and 3. The mass content of LiPF6 is 14%, and the rest is ethylene carbonate, propylene carbonate, and propyl propionate (mass ratio 2:1.8:4).
[0079] Then, the wound body and 3.2g of electrolyte were placed in an aluminum laminate case. The opening of the case was heat-sealed, and a secondary battery was made through steps such as formation and capacity measurement. The secondary battery was a pouch-shaped secondary battery with a width of 35mm, a height of 48mm, and a thickness of 5mm.
[0080] Table 1 Table 1-1 Additives
[0081] serial number name Additive 1 Pentaerythritol tetrabenzoate Additive 2 Trimethyl citrate Additive 3 Triethyl citrate Additive 4 Tributyl citrate Additive 5 Sodium ditridecyl sulfosuccinate
[0082] Table 1-2 Additive Code
[0083]
[0084]
[0085] Test Method
[0086] Flexibility of positive electrode
[0087] A rod with different diameters is placed on the current collector side of the positive electrode to be made, and the positive electrode is wound onto the rod to evaluate whether the positive electrode composite material layer is broken. The smaller the diameter of the rod, the more excellent the flexibility of the positive electrode is. When the flexibility of the positive electrode is excellent, the peeling of the positive electrode composite material layer can be suppressed, so the cycle characteristics of the secondary battery are excellent.
[0088] A: Not broken by a rod with a diameter of 1.2 mm.
[0089] B: Not broken by a rod with a diameter of 1.5 mm.
[0090] C: Not broken by a rod with a diameter of 2 mm.
[0091] D: Not broken by a rod with a diameter of 3 mm.
[0092] E: Not broken by a rod with a diameter of 4 mm.
[0093] Internal resistance at low temperature
[0094] The lithium ion secondary battery was allowed to stand for 5 hours at 25°C, and the thickness (d0) of the battery was measured. Next, constant current-constant voltage charging (CC-CV charging) was performed at 1C to 4.6V (cut-off condition 0.05C), and constant current discharge (CC discharge) was performed at 1C to 3V, and this operation was performed for 500 cycles at 25°C.
[0095] After 500 cycles, CC-CV charging was performed at 1C (cutoff condition 0.05C) to 4.6V at -20°C, and the thickness (d1) of the battery in the charged state was measured. Then, the thickness increase rate at low temperature was calculated = {(d1-d0) / d0}×100(%), and the evaluation was performed according to the following criteria. The smaller the value of the thickness increase rate at low temperature, the more the internal resistance of the secondary battery at low temperature is suppressed.
[0096] A: The thickness increase rate at low temperature is less than 5%.
[0097] B: The thickness increase rate at low temperature is 5% or more and less than 8%.
[0098] C: The thickness increase rate at low temperature is 8% or more and less than 10%.
[0099] D: The thickness increase rate at low temperature is 10% or more.
[0100] High temperature storage characteristics
[0101] For the prepared lithium-ion secondary battery, after charging to 4.6V by the constant current method of 0.1C at 25°C, it was stored at 80°C for 100 hours. The open circuit voltage (OCV) before the start of storage at 80°C and the OCV of the cell after storage at 80°C for 100 hours were measured, and the ratio of the OCV after storage at 80°C for 100 hours to the OCV before storage at 80°C was calculated as the OCV maintenance rate, and evaluated using the following criteria. The larger the OCV maintenance rate, the better the high-temperature storage characteristics, that is, the better the life characteristics.
[0102] A: The OCV maintenance rate is 99.0% or more.
[0103] B: The OCV maintenance rate is 98.5% or more and less than 99.0%.
[0104] C: The OCV maintenance rate is 98.0% or more and less than 98.5%.
[0105] D: OCV maintenance rate is less than 98.0%.
[0106] Test Results
[0107] Table 2
[0108]
[0109]
[0110] Table 3
[0111]
[0112]
[0113] In Tables 2 and 3, relative to 100 parts by mass of the electrolyte, a is the mass fraction of the compound having a sulfur-oxygen double bond, b is the mass fraction of lithium difluorophosphate, and the numbers in () represent the mass fractions of the corresponding substances.
[0114] When the positive electrode active material layer includes a positive electrode active material and polyamide-imide, and the electrolyte includes a compound having a sulfur-oxygen double bond and lithium difluorophosphate, not only can the flexibility of the positive electrode be improved, but also the internal resistance of the secondary battery at low temperatures can be reduced and the storage characteristics at high temperatures can be improved. In particular, when the electrolyte includes at least two of the above-mentioned compounds having a sulfur-oxygen double bond, the storage characteristics of the secondary battery at high temperatures can be further improved.
[0115] In particular, when the positive electrode active material layer also includes an auxiliary agent, such as pentaerythritol tetrabenzoate, trimethyl citrate, triethyl citrate, tributyl citrate or sodium ditridecyl sulfosuccinate, the impedance of lithium difluorophosphate forming a film on the positive electrode surface can be suppressed from being too large, and the flexibility of the positive electrode can be further improved.
[0116] In particular, when the electrolyte also contains additive C, the inventors unexpectedly discovered that additive C not only inhibits the decomposition of polyamideimide during the charge and discharge process, but also can further reduce the impedance of compounds with sulfur-oxygen double bonds and lithium difluorophosphate coatings, thereby further reducing the internal resistance of the secondary battery at low temperatures and improving the storage characteristics at high temperatures.
[0117] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics in the present application may be combined in one or more embodiments or examples in any suitable manner.
[0118] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A secondary battery, characterized in that: It includes: A positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material and polyamideimide, and the electrolyte comprises a compound having a sulfur-oxygen double bond and lithium difluorophosphate; Wherein, relative to 100 parts by mass of the electrolyte, the compound having a sulfur-oxygen double bond is in an amount of 0.05 parts by mass to 2.9 parts by mass, and / or the lithium difluorophosphate is in an amount of 0.02 parts by mass to 0.59 parts by mass.
2. The secondary battery according to claim 1, characterized in that: The positive electrode active material layer further comprises an auxiliary agent, and the auxiliary agent comprises at least one of pentaerythritol tetrabenzoate, trimethyl citrate, triethyl citrate, tributyl citrate or sodium ditridecyl sulfosuccinate.
3. The secondary battery according to claim 1, characterized in that: The compound having a sulfur-oxygen double bond includes sulfonate and / or sulfate.
4. The secondary battery according to claim 3, characterized in that: The sulfonate ester includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone or methylene methane disulfonate.
5. The secondary battery according to claim 3, characterized in that: The sulfate ester comprises at least one of ethylene sulfate or propylene sulfate.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The electrolyte further includes an additive C, and the additive C includes at least one of adiponitrile, hexamethyldisiloxane, 1,3-divinyltetramethyldisiloxane, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium tetrafluoro(oxalato)phosphate or lithium difluorobis(oxalato)phosphate.
7. The secondary battery according to claim 6, characterized in that: The total amount of the additive C is 0.1 to 3 parts by mass relative to 100 parts by mass of the electrolyte.
8. The secondary battery according to claim 6, characterized in that: Wherein, relative to 100 parts by mass of the electrolyte, at least one of the following is satisfied: 1) The adiponitrile is 0.1 to 2.4 parts by mass; 2) the hexamethyldisiloxane is 0.01 to 0.6 parts by mass; 3) the 1,3-divinyltetramethyldisiloxane is 0.01 to 1 parts by mass; 4) the lithium bis(oxalato)borate is 0.01 to 0.5 parts by mass; 5) the lithium difluoro(oxalato)borate is 0.01 to 0.5 parts by mass; 6) The lithium tetrafluoro(oxalato)phosphate is in an amount of 0.01 to 0.5 parts by mass; 7) The lithium difluorobis(oxalato)phosphate is in an amount of 0.01 to 0.7 parts by mass.
9. An electronic device, characterized in that: It includes the secondary battery according to any one of claims 1 to 8.